Time-since-death and its effect on wood from beetle-killed Engelmann spruce in southwest Colorado - Vaughan, Damon, author; Mackes, Kurt, advisor; Wei, Yu, committee member; Rastall, Patrick, committee member (Colorado State University. Libraries, 2016)
Spruce beetles (Dendroctonus rufipennis) have caused extensive mortality on 1.5 million acres in Colorado during the current epidemic. There is considerable interest in harvesting treatments aimed at removing dead trees for reasons of fire risk, watershed health, and human dimensions. The byproducts from these treatments can either be viewed as a difficult and costly disposal problem or an opportunity for the recovery of forest products. However, a major barrier to the latter option is the lack of knowledge about how the material changes with time standing dead. Ten plots were selected on the Rio Grande National Forest (RGNF), from which 86 Engelmann spruce (Picea engelmannii) trees were felled and sampled. Tree rings were analyzed to determine Time-Since-Death (TSD) on all study trees. TSD and other variables such as diameter, elevation, and bark retention were used to develop models predicting the deterioration rate from beetle mortality (seasoning check, heart rot, and sap rot). In a separate mill study, eleven trees from the RGNF were milled to dimensional lumber to determine the lumber tally, prevalence of blue stain, and lumber grade breakdown. Checking was found to be most strongly correlated with tree diameter, and the effect of TSD was most pronounced at larger diameters. Higher elevations and increased bark retention served to reduce or slow checking. Sap rot was found to increase with TSD, but heart rot was not. Many study trees had moisture contents suitable for the development of rot. In the mill study, older dead trees produced a lower percentage of select structural lumber than control trees. Net Scribner was a poor predictor of lumber tally; gross Scribner and product potential cubic were more accurate. Results from this study may help land managers maximize sawtimber recovery by prioritizing treatment areas. Information such as tree diameter, TSD, and elevation will allow foresters to better differentiate stands that have already been subject to severe deterioration from those that will in short order.